Analysis of Turbulent Lean Premixed Methane-Air Flame Statistics at Elevated Pressures - YILMAZ, BARIŞ (AMER CHEMICAL SOC, 2017)
Combustion takes place within turbulent environments and under pressurized conditions in most industrial applications, for instance, gas turbines and internal combustion engines. The mixing of fuel and oxidizer is enhanced by turbulence, so that combustion will be more efficient. In addition, during combustion, heat is released; therefore, it causes flow instability as a result of gas expansion and high gradients of temperature. The interaction of turbulence and combustion under pressurized conditions may lead to modifications and even. disruption of the flame. There are still ongoing studies on the prediction of flame and flow statistics, which are crucial for the stable operation of high-pressure combustion systems. In the present study, the aim is to investigate the influence of elevated pressures on the structure of turbulent premixed methane air flames, within the range from atmospheric to 0.9 MPa, by numerical modeling and experimental validation. The computations are performed initially for the cold flow field and then for the reactive flow statistics using the Fluent software. For the cold flow case results, it is found that the velocity potential core region extends until three diameters downstream from the burner exit and the decay rate decreases with increasing pressure. However, in the reactive case simulations, the decay in the velocity profiles is not observed as a result of gas expansion through the flame front, similar to the experiments. The turbulent flame front statistics in terms of the flame front location, the flame brush thickness, and the flame surface density (FSD) have been computed. The flame tip location and flame brush thickness are found more downstream and thicker at elevated pressures, respectively. Moreover, both the profiles and peak values of FSD are well-captured for various pressure conditions in computations compared to the measurements.
Keywords: BURNING VELOCITY; SPEED; COMBUSTION; SCALE